Experimental study for determining parameters of pulse conducting electromagnetic interference in vehicle’s onboard network KAMAZ 5350 - K. V. Khatsevskiy; A. A. Sidorenko; V. E. Belyakov; S. V. Roslov (Омский научный вестник)
The widespread introduction of high-tech electronic products designed to work on military vehicles establishes the need to strictly meet the requirements for their electromagnetic compatibility for conductive interference in on-board networks. The article analyzes the sources of electromagnetic interference in the vehicle’s onboard network. The paper presents the results of experimental studies to determine the parameters of pulsed conductive electromagnetic interference in the on-Board network of the KAMAZ 5350 car and determine their compliance with the requirements for electromagnetic compatibility.